ANAEMIA PREVENTION AND FACTORS ASSOCIATED WITH USE OF IRON SUPPLEMENT AMONG PREGNANT WOMEN IN IBADAN NORTH LOCAL GOVERNMENT AREA, NIGERIA (2015)
Anaemia is a public health problem affecting an estimated 3.5 billion people worldwide and at least 50% of pregnant women in Africa. Nigeria has a relatively high prevalence of anaemia in pregnancy despite ameliorating measures including use of iron supplementation as prophylaxis. This study was conducted to assess anaemia prevention practice and factors associated with use of iron supplements among pregnant women in Ibadan North Local Government Area of Oyo State, Nigeria.Six primary health centers were randomly selected from ten primary health centers in Ibadan North L.G.A. A total of 450 consenting pregnant women were interviewed from the six selected primary health centers based on the proportion of pregnant women that attended antenatal clinic in each PHC. An interviewer-administered semi-structured questionnaire which included knowledge score of 0-30 categorized into good (70-100 %) and poor (0-69 %.) and also practice score of 15-75 categorized into poor (15-33) and good (34-75). Among the practice scores, compliance to prescription was checked using a compliance score of 3-15 of the total score categorized into low (3-9) and high (10-15). Descriptive statistics, Chi-square and t-tests, and logistic regression were used for data analysis at 5% level of significance.The mean age of the respondents was 26.7'4.6years. Majority (93.8%) were Yoruba, self-employed (79.1%) and Muslims (58.0%). Many (79.3%) had secondary education and (80%) earned less than N20, 000 monthly while few (4.0%) were unemployed. Most (65.3%) had 2 or more children (Multigravidas) while (34.7%) just had first pregnancy (primigravidas). Majority (84.7%) of respondents had good knowledge of anaemia prevention with a mean ('S.D) knowledge score of 23.5 ' 5.5. The unemployed were less (OR: 0.10; CI= 0.03-0.40, p-value 0.001) likely to have good knowledge of anaemia prevention than the employed while respondents with primary and secondary education were about five (OR: 4.70; CI= 1.05-21.11, p-value 0.044) and six times respectively (OR: 6.15; CI=1.49-25.45, p-value 0.012) more likely to have good knowledge of anaemia prevention than those without any formal education. The unemployed were less likely to have good anaemia prevention practices than the employed (OR: 0.04; CI = 0.003-0.46, p-value 0.010) and those with 2 or more children (multigravidas) were about five times more likely to have good anaemia prevention practices than the primigravidae (OR: 5.01; CI= 1.56-16.09, p-value 0.007). Although majority of the respondents (93.3%) used iron supplements, compliance to prescription (57.3%) was relatively low. Respondents with secondary and tertiary education were about seven (OR: 6.65; CI= 1.15-38.57, p-value 0.035) and 24 times respectively (OR: 24.33; CI=2.06-287.9, p-value 0.011) more likely to use iron supplements than those without any formal education. And respondent with 2 or children (multigravidas) were about three times (OR: 3.10; CI=1.08-8.84, p-value 0.035) more likely to use Iron-Folic acid supplements than the primigravidae.Socio-economic factors were determinants of anaemia prevention practice among pregnant women. There is therefore need for timely economic empowerment and educational interventions to address these challenges.